Neuroprotective effects of alkaloids from Piper longum in a MPTP-induced mouse model of Parkinson's disease. (October 2015) - Bi, Ying; Qu, Peng-Cheng; Wang, Qing-Song; Zheng, Li; Liu, Hao-Long; Luo, Rong; Chen, Xiao-Qing; Ba, Yin-Ying; Wu, Xia; Yang, Hui
Abstract Context: Alkaloids of Piper longum L. (Piperaceae) (PLA) include piperine and piperlonguminine. Piper longum and piperine have multiple biological properties including antioxidant activity. Objective: The present study investigated the neuroprotective effects of PLA in a MPTP-induced mouse model of Parkinson's disease. Materials and methods: PLA was prepared by extracting the dry seed of P. longum using 85% ethanol. Adult male C57BL/6 mice were divided into eight groups of 12 rats each. Experimental and control groups received an equivalent volume of saline, 0.5% CMC-Na, and 0.1% Tween 80, treated groups received oral PLA (30, 60, and 120 mg/kg), other groups treated with piperine (60 mg/kg) or Madopar (50 mg/kg). The PLA prevention group (PLA-Pr) administrated PLA (120 mg/kg) for 1 week before MPTP challenged. Except for the PLA-Pr group, others were treated for seven consecutive weeks. Parkinson's disease was induced by injecting MPTP intraperitoneally (25 mg/kg) twice weekly for five consecutive weeks. Dopaminerigic (DA) neurons and their metabolism were detected by UFLC-MS/MS. Tyrosine hydroxylase (TH)-immunohistochemistry assay and Western blotting were performed. The antioxidant enzymatic levels were determined by kit-based assays. Results: The LD50 value of PLA was determined at 1509 mg/kg of body weight. PLA (60 mg/kg) can significantly increase total movement time and distance (p < 0.05), increase levels of DA (p < 0.05) and DOPAC (p < 0.05), increase glutathione (GSH) level and superoxide dismutase (SOD) activity (p < 0.05), and decrease the lipid peroxidation of malondiadehycle (MDA) (p < 0.05) in PLA-treated groups as compared with the control group. Discussion and conclusion: Our results indicate that PLA possesses neuroprotective effects and has ameliorative properties in dopaminergic neurons.